Understanding price developments and consumer price indices in south-eastern Europe - Sabine Herrmann; Eva Katalin Polgar (European Central Bank (ECB), 2007)
The primary goal of monetary policy in most economies of the world is to achieve and maintain price stability. This paper evaluates price developments and consumer price indices in south-eastern European countries, i.e. countries that have either recently joined the EU or are candidate or potential candidate countries. It is motivated by the fact that, in transition countries, inflation has generally been higher and more volatile than in advanced economies. The analysis reveals that the subindex housing/energy appears to be the main driving force behind overall inflation in the region. In most of the countries under review, administered prices prove to be an important factor in consumer price developments, with their weights increasing over time. Inflation volatility in south-eastern Europe is significantly higher than in the euro area. While this is partly due to a higher level of inflation, it also reflects a more pronounced share for the most volatile sub-indices as well as the marked impact of administered prices on the overall price index, a phenomenon which has also been seen in the central and eastern European countries. While in most south-eastern European countries no HICP has been calculated yet, there is little evidence suggesting that the future use of the HICP will result in a systematic change in inflation patterns in the respective countries. However, as deviations have been observed in a few countries for certain periods, without further information on the structure of the respective national CPI and the HICP such differences cannot be fully excluded.
Keywords: E21; O52; O57; P22; 330; South-eastern Europe; inflation developments; inflation volatility; consumer price indices; HICP; administered prices.; Inflation; Preisindex; EU-Mitgliedschaft; Südosteuropa; Türkei